Risk management support and organizational performance: The role of enterprise risk management as mediator / Azreen Roslan, Nur Diyana Yusoff and Hayati Mohd Dahan - Roslan, Azreen; Yusoff, Nur Diyana; Mohd Dahan, Hayati (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
Risk is inherent in all parts of the organization and if it is not efficiently managed by the senior management it will affect the confidence and expectations of the stakeholders. Enterprise Risk Management (ERM) is said as a best practice technique to evaluate and manage all these risks in this new economic reality. Therefore, organizations practicing ERM are more prepared in managing the feasible threats. In fact, there is a general consensus by scholars and researchers that organizations practicing ERM will improve the organizational performance. However, empirical evidence regarding this matter is still considered scarce. As such, the purpose of this paper is to investigate the mediating effect of ERM on risk management support and organizational performance among public listed companies.